Comparação entre o processo de virulência em Paracoccidioides brasiliensis e P. lutzii com utilização de modelo alternativo de bioensaio e knockdown gênico - Machado, Gabriel Capella [UNESP] (2015)
Paracoccidioidomycosis (PCM), an important systemic mycosis in Latin America, is caused by the cryptic species Paracoccidioides brasiliensis and P. lutzii. How these species differ in their virulence factors is still unknown and needs to be properly evaluated. While the role of PbGP43, which codes gp43, as a virulence factor is relatively well established for P. brasiliensis, the same is not true for its ortholog in P. lutzii, namely PlP43. PbGP43 and PlP43 present differences in their nucleotide sequences, expression levels, epitope occurrence and influences on PCM diagnosis. Herein, we obtained PbGP43 and PlP43 knockdown strains by antisense RNA technology combined with ATMT, in order to comparatively evaluate their effects on virulence, employing the alternative experimental host Galleria mellonella larvae. Our results suggest that p43 is important in the P. lutzii infectious process, as previously demonstrated by gp43 in P. brasiliensis. We confirmed G. mellonella as a useful model for studying P. brasiliensis and P. lutzii virulence, since it reflects variation between inoculum size and different strains, as well as between wild-type and respective knockdown transformant strains. Virulence levels may vary among isolates of the same species, probably reflecting that the physiological condition is more important than the species effect. Re-isolation of Paracoccidioides from experimentally infected G. mellonella larvae is possible and might be useful for epigenetic studies related to infection